2021
DOI: 10.5650/jos.ess20359
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Characterization of <i>Sesbania cannabina</i> (Retz.) Pers. (Dhaincha) Seed Oil for Potential Engineering Applications

Abstract: IntroductionThe genus Sesbania of family Fabaceae is comprised of around 60 species of annuals, perennials, herbs, shrubs and trees that are distributed over tropical and subtropical regions of the world. Sesbania aculeata (synonym Sesbania bispinosa, Prickly sesban, Dhaincha) , Sesbania cannabina (common sesban, Yellow pea bush, Dhaincha) , Sesbania drummondii (Rattlebox) , Sesbania grandiflora (vegetable hummingbird, Agathi, Agasti) , Sesbania rostrata (Manila Agathi, new Dhaincha) , Sesbania sesban (Egyptia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Hussain and Kumaresan (2014) with GC-MS analysis of S. grandiflora leaves methanolic extracts revealed that these mainly composed of oxygenated hydrocarbons and phenolic hydrocarbons. Palmitic acid (11.8%), 9-hexadecenol (9.0%) and octadecanoic acid were the major compounds having pesticidal activities (Gopalakrishnan and Vadivel, 2011;Geetha et al, 2013;Mishra et al, 2021). No pupal mortality and malformations were recorded in these treatments.…”
Section: Resultsmentioning
confidence: 98%
“…Hussain and Kumaresan (2014) with GC-MS analysis of S. grandiflora leaves methanolic extracts revealed that these mainly composed of oxygenated hydrocarbons and phenolic hydrocarbons. Palmitic acid (11.8%), 9-hexadecenol (9.0%) and octadecanoic acid were the major compounds having pesticidal activities (Gopalakrishnan and Vadivel, 2011;Geetha et al, 2013;Mishra et al, 2021). No pupal mortality and malformations were recorded in these treatments.…”
Section: Resultsmentioning
confidence: 98%